Uso de adubos verdes para fitorremediação de solos contaminados com amicarbazone - Mello, Antônio José Plácido de (2018)
The objective was to evaluate the behavior of different plant species in phytoremediation of soil contaminated with amicarbazone in a bean bioindicator plant (Phaseolus vulgaris L.). Two experiments were carried out in vegetation house of the CECA –Agricultural Sciences Center the Federal University of Alagoas (UFAL), in Rio Largo - Alagoas, The first experiment was installed from January 2016 to July 2016, using pots of 10 dm3 of soil. The treatments were composed of 09 species of plants: Black Mucuna cv mucuna black (Mucuna pruriens); Crotalaria breviflora cv common (Crotalaria breviflora DC); Calapogonium sp cv common (Callopogonium mucunoides Desv); Lab Lab cv songai (Dolichos lablab L); Beans guandu cv fava largo (Cajanus cajan (L) Millsp); Turnip forage cv sl 1000cv (Raphanus sativus L); Crotalaria spectabilis (Crotalaria spectabilis Roth); (Leucaena leucocephala (Lam) de wit) and a treatment without culture (control) and four doses of amicarbazone (0; 0.5; 1.0; 1.5 kg.ha-1), respectively (0; 350; 700; 1050 g.a.i.ha-1). The experimental design was a randomized complete block design in a 10 X 04 factorial scheme with four replications. The second experiment was installed in the period from September 2016 to June 2017, using pots 10 dm3 of soil. The treatments were composed of 03 plant species: Mucuna black cv mucuna preta (Mucuna pruriens); Crotalaria spectabilis (Crotalaria spectabilis Roth); Leucaena (Leucaena leucocephala (Lam) de wit) and a treatment without culture (control) and four doses of amicarbazone (0; 0.5; 1.0; 1.5 kg.ha-1), respectively (0; 350 ; 700; 1050 g.a.i ha-1). The experimental design used was a randomized complete block design in a 4 X 04 factorial scheme with four replications. On the 30th and 60th days, the following species were observed in the leaves of bean cultivated in succession: notes of Leaf Phytotoxicity Symptoms, Total Chlorophyll content in laboratory, Electron Transfer Rate (ETR), SPAD Index, Falker Chlorophyll Index (ICF) , Dry Matter and Determination of Herbicide Concentration in soil (in the second experiment). Multivariate data analysis was performed. The results of the tests allowed to conclude presented simple correlations in the observed variables and in the matritional correlations. With the species they present potential phytoremediation effect, mainly the black Mucuna, Crotalaria breviflora, Crotalaria spectabilis, forage turnip. High similarity between SPAD Index and Falker Chlorophyll Index and Herbicide Concentration in soil, Phytotoxicity, Electron Transfer Rate and Dry Matter. High matritional and simple correlations between variables, mainly in the first trial.